ChemInform Abstract: A Mild Ni/Cu‐Catalyzed Silylation via C—O Cleavage. Issue 34 (26th August 2014) - Zarate, Cayetana; Martin, Ruben
Abstract Advantages of the title method are mild conditions, robustness, and wide substrate scope allowing the coupling of Csp2—O and even Csp3—O bonds with similar efficiency.